Diseño de la planta de biogás en el fundo Miraflores de la Universidad Nacional de San Martín – Tarapoto - López Gutiérrez, Claudio Iván (2002)
Biogas is an ecologically clean fuel that is produced by the action of anaerobic bacteria that break down organic matter (so much dung as foliage). Apart from gas produced solid bio-fertilizer and liquid. This fuel can be used both for cooking and for the operation of combustion engines, refrigerators that use kerosene as a fuel as well as for heating and lighting. The potential of raw materials in the rural area make it possible to develop this project, which consists of a floor of a flat where all the funds from organic matter will be stored suppliers and the bio-fertilizer that will be subsequently marketed. The structure of the biodigestor has a volume of 25 m3 to produce a volume of 3m 3 of gas per day. The plant possesses. Plumbing and electrical systems that guarantee the comfort of the operators of the plant in the performance of their work. The electricity...